Strain derivative of thermoelectric properties as a sensitive probe for nematicity - F. Caglieris (Nature Portfolio, 2021)
Abstract The nematic instability is an undebatable ingredient of the physics of iron-based superconductors. Yet, its origin remains enigmatic as it involves a fermiology with an intricate interplay of lattice-, orbital-, and spin degrees of freedom. It is well known that thermoelectric transport is an excellent probe for revealing even subtle signatures of instabilities and pertinent fluctuations. In this paper, we report a strong response of the thermoelectric transport properties of two underdoped 1111 iron-based superconductors to a vanishingly small strain. By introducing the strain derivative of the Seebeck and the Nernst coefficients, we provide a description of the nematic order parameter, proving the existence of an anisotropic Peltier-tensor beside an anisotropic conductivity tensor. Our measurements reveal that the transport nematic phenomenology is the result of the combined effect of both an anisotropic scattering time and Fermi surface distortions, pointing out that in a realistic description, abreast of the spin fluctuations also the orbital character is a fundamental ingredient. In addition, we show that nematic fluctuations universally relax in a Curie–Weiss fashion above T S in all the elasto-transport measurements and we provide evidences that nematicity must be band selective.